Comparative Pollution Index Assessment of Seawater Quality at Two Coastal Beaches in Lamongan - Nasihah, Mimatun; Zufar Assahbantar, Azhar; Fauzi, Mohammad; Febrianto, Ahmad; Dwi Yanti, Sylvia; Niswatin, Nanis (Biotropika: Journal of Tropical Biology, 2026)
Different coastal activities may exert varying environmental pressures on marine water quality, even in geographically adjacent areas. This study aimed to compare the marine water quality at Kemantren Beach and Lorena Beach, Paciran District, Lamongan Regency, which are characterised by different coastal activity pressures, and to assess the water quality status using the Pollution Index (PI). This research employed an observational approach with a descriptive-comparative design. The marine water quality parameters included Total Dissolved Solids (TDS), Total Suspended Solids (TSS), pH, Dissolved Oxygen analysed (DO), turbidity, and temperature. Data were analysed descriptively and comparatively using the Mann–Whitney U test and evaluated against marine water quality standards based on Government Regulation No. 22 of 2021, Appendix VIII. The results showed that all measured water quality parameters at both locations were within the permissible limits for marine tourism and marine biota. However, distinct differences in water quality characteristics were observed between the two beaches. Kemantren Beach exhibited higher TSS and turbidity values compared to Lorena Beach, which were associated with fishing boat activities and sediment resuspension. Pollution Index analysis indicated that both sites were classified as lightly polluted, with a higher PI value at Kemantren Beach. These findings suggest the presence of early-stage environmental pressure resulting from different anthropogenic activities. This study demonstrates that the Pollution Index approach provides a comprehensive assessment of marine water quality and can serve as a scientific basis for sustainable coastal management.